Reading Corner With The Theme "Exploring the World of Books Together" at SDN Kertawinangun 1 Cirebon - Asep Kosasih; Yeyet Daryati; Suwandi; M. Anissul Fata; Cicin Yuningsih; Eva Sri; Irgi Muhamad (SOCIRCLE : Journal Of Social Community Services, 2024)
Background: The digital era requires education stakeholders to continue to improve to balance student needs according to technological developments. One of the efforts made is through the Reading Corner program, namely the use of classroom corners as mini libraries to develop students' reading skills. Objective: Reading Corner activities aim to encourage interest in reading from an early age, improve literacy skills, broaden horizons and knowledge, and encourage students' creativity and imagination. Method: The technical implementation of Reading Corner activities is divided into 3 stages, namely the preparation stage, socialization activities, and implementation activities. Results: Through the Reading Corner, it is hoped that it can instill a reading culture and positive habits related to a love of reading in students, so that they are better able to respond to life's challenges in the future. Conclusion: The Reading Corner is a form of the school's commitment to supporting the 15-minute Compulsory Reading Movement launched by the Government. ABSTRAK Latar Belakang: Era digital menuntut para pemangku pendidikan untuk terus berbenah menyetarakan kebutuhan siswa sesuai perkembangan teknologi. Salah satu upaya yang dilakukan adalah melalui program Pojok Baca, yaitu pemanfaatan pojok kelas sebagai perpustakaan mini untuk mengembangkan daya baca anak didik. Tujuan: Kegiatan Pojok Baca bertujuan untuk mendorong minat baca sejak dini, meningkatkan keterampilan literasi, memperluas wawasan dan pengetahuan, serta mendorong kreativitas dan imajinasi siswa. Metode: Teknis pelaksanaan kegiatan Pojok Baca terbagi menjadi 3 tahap, yaitu tahap persiapan, kegiatan sosialisasi, dan kegiatan implementasi. Hasil: Melalui Pojok Baca, diharapkan dapat menanamkan budaya membaca dan kebiasaan positif terkait gemar membaca pada siswa, sehingga mereka lebih mampu menjawab tantangan hidup di masa mendatang. Kesimpulan: Pojok Baca merupakan wujud komitmen sekolah dalam mendukung Gerakan Wajib Membaca 15 menit yang dicanangkan oleh Pemerintah.